The Concept of Sociocultural Code in the Context of National Security Discourse - Alexey A. Lagunov; Svetlana Yu. Ivanova (RUDN Journal of Philosophy, 2025)
The study analyzes the concept of socio-cultural code, which has insufficient definition in modern social and humanitarian knowledge. The author’s interpretation of this concept is offered. It is based on the methodology of philosophical personalism, in which personality is presented as a source of relatively free and creative spiritual and practical activity. The product of this activity is culture, which in turn has a significant impact on the formation of personality. The expediency of understanding the socio-cultural code as a set of worldview constants, both conscious and subconscious, is argued. The relationship of the concept of socio-cultural code with such traditional concepts of social philosophy as “public consciousness”, “worldview”, “mentality” is clarified. The authors come to the conclusion that the concept of socio-cultural code in its scope is intermediate between mentality and public worldview. It is broader than the first, but narrower than the second, since the public worldview may also include non-constant elements that quickly transform or even disappear in socio-historical time. It is noted that the concept of socio-cultural (cultural) code directly relates to the sphere of ensuring national security, and this is indicated by its use in the Strategy of the State National Policy of the Russian Federation for the period up to 2025. In the Strategy, it is given a predominantly ideological significance. It is asserted that it is groundless to classify even some elements of the socio-cultural code as a priori, innate qualities of representatives of a particular community. All its elements without exception are of an a posteriori nature, manifesting themselves as properties of individuals that are formed in the processes of their socialization and enculturation. The recognition of the fundamentally a posteriori nature of both the socio-cultural code and public mentality and worldview, according to the authors, allows us to get rid of the illusory reliance on the nature of things and seriously focus attention on the reproduction of culture as the most important factor in ensuring national security. In addition to measures to strengthen political and economic sovereignty, it must necessarily include a set of actions aimed at maintaining the continuity of public consciousness.